Expressões fixas do português formadas a partir de nomes gerais: Aspectos lexicais e variacionistas - Luanna de Sousa do Nascimento Oliveira (2017)
This thesis intended to analyze the lexical and the diatopic variation of fixed expressions (FEs) of Brazilian Portuguese made of general nouns. Although the FEs have the crystallization as their main feature, they have degrees of fixity. In this context, expressions such as não falar coisa com coisa and não dizer coisa com coisa have the same meaning (disconnected speech); there is no variation concerning the general noun coisa (thing), but there are changes in the other components of the FE. On the other hand, one can observe substitutions of the general noun coisa in other FEs, such as dar uma coisa and dar um negócio, in which the meaning of losing the senses is kept despite the variation. The general nouns are defined by Halliday and Hasan (1995 [1976], p. 274) as a class of nouns in between the open classes and the closed ones which have important cohesive function since they comprehend minimum referential semantic content. In relation to the diatopic variation in Brazilian territory, as observed by Fulgêncio (2008, p. 369), the use of some FEs can be considered typically regional, because there is geographic variation. The nouns coisa, negócio, trem, troço, pessoa, homem, mulher, cara and lugar were selected to be analized. The corpora were extracted from the dictionaries Aulete Digital, Ferreira (2010), Houaiss (2009) and Rocha (2011) and from 411 transcriptions from the projects O uso de nomes gerais nos falares mineiros, PORCUFORT, and Grupo Discurso & Gramática e Norma Urbana Oral Culta, in a total of 1,585,357 words. It was verified that, regarding the elements that vary in the same syntactic context of the general nouns, the lexical variation is restricted to the same semantic field and is limited to the demonstratives pronouns esse / este / aquele, to the verbs ser / ter, and to the insertion/removal of elements, such as the adverb of place lá and the definite article o. The general noun variation itself happens more easily in conversational markers. Regarding the diatopic variation, following the indication of the dictionaries concerning the general noun trem, the conversational markers esse trem de and esse trem todo are restricted to the Mineiro way of speaking, demonstrating a possible indication of regional use of the FE.